Wisata Olahraga di Gorontalo Indonesia - Pauweni, Mirdayani; Rahayu, Tandiyo; Winarno, M E; Setyawati, Heny; Pomatahu, Aisah R; Pakaya, Rosbin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2023)
The research aims to identify the potential for sports tourism in Gorontalo. This qualitative descriptive research applies semi-structured interviews, observations (direct visits), and assessments using MSPDM and DODTWA analysis. The research findings show that Gorontalo has seven leading sports tourism destinations that utilize marine and mountain sports as attractions. Good tourism elements also support these superior destinations. Additional efforts are needed to increase the development of goals to become independent and the feasibility level of each tourism element. In conclusion, several tourist destinations in Gorontalo are superior and require additional efforts to increase these destinations' levels. Keywords: Potential, Sports Tourism, Destinations, Tourism Elements